THE ELECTRON LOCALIZATION FUNCTION: A TOOL FOR LOCATING FAVORABLE PROTON DOCKING SITES IN THE SILICA POLYMORPHS - Gibbs G.V.; Cox D.F.; Boisen Jr.M.B.; Downs R.T.; Ross N.L. (My University, 2003)
The ELF electron localization function was used to locate regions ascribed to localized nonbonding electrons as favorable docking sites for hydrogen atoms in coesite, quartz, and stishovite. A mapping of the function for a series of representative hydroxyacid disilicate and cyclosiloxane molecules indicates that the nonbonding regions on the bridging oxide anions involved in narrow SiOSi angles are more favorable as docking sites than those involved in wide angles. It also indicates that the nonbonding regions associated with the nonbridging oxide anions comprising surface SiOH dangling bonded interactions are likewise favorable docking sites. ELF descriptions of the nonbonding and bonding regions for coesite and quartz were found to be similar to those obtained for the molecules. For a protonated coesite crystal, the function was also used to deduce the positions of the model H atoms of a defect ν(OH)4 group where ν is the vacancy left by Si. The positions of the H atoms were found to be in reasonable agreement with those determined in an infrared study, particularly for those bonded to anions involved in narrow SiOSi angles. A mapping of the ELF indicates that the OH vector reported for stishovite is oriented nearly perpendicular (92.5°) to [001], as found in infrared studies. The nonbonding region displayed by the function was used to locate the position of the H atom at a distance of 0.96 A from the nonequivalent oxide anion comprising the shared edge of the silicate octahedra. The positions of model hydrogen atoms comprising a potential defect ν(OH)4 group in quartz were also deduced on the basis of the positions of the local maxima of the nonbonding regions. When used in conjunction with spectroscopic methods, the strategy used in this study should be useful in locating protons in Earth materials with trace amounts of H. Maxima ascribed to regions of bonding and nonbonding electrons displayed in the ELF maps were found to be in close correspondence with those displayed in valence, deformation, and Laplacian electron-density distributions. Collectively, these results indicate that the electron density is localized in the nonbonded regions of the anions involved in the narrow SiOSi angles (angles less than ~150°) in silica polymorphs like quartz and coesite and much less so for the anions involved in wider angles.